2010
DOI: 10.1007/s00482-010-1008-x
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin und postoperative Hyperalgesie

Abstract: Numerous studies support the theory that pregabalin causes an antihyperalgesic effect, which could be potentially beneficial in a perioperative setting. By binding to calcium channels pregabalin reduces the release of excitatory neurotransmitters and therefore inhibits central sensitization. Animal studies clearly demonstrated the antihyperalgesic potency of pregabalin but human experiments are, however, inconclusive. Clinical studies with quantitative sensory testing have not yet been published. Although stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…10 A recent review of this topic concluded that there is substantial evidence from basic research that pregabalin has an impact on the prevention of postoperative hyperalgesia; however, clinical data are insufficient to allow any conclusion. 8 In this study, we aimed to demonstrate the effect of a single, preoperative dose of pregabalin on postoperative opioid consumption, hyperalgesia, and pain sensitivity.…”
Section: Accepted For Publication: 5 December 2011mentioning
confidence: 99%
“…10 A recent review of this topic concluded that there is substantial evidence from basic research that pregabalin has an impact on the prevention of postoperative hyperalgesia; however, clinical data are insufficient to allow any conclusion. 8 In this study, we aimed to demonstrate the effect of a single, preoperative dose of pregabalin on postoperative opioid consumption, hyperalgesia, and pain sensitivity.…”
Section: Accepted For Publication: 5 December 2011mentioning
confidence: 99%
“…The authors should be congratulated to their interesting work, which showed benefits in reducing postoperative pain and analgesic requirements. Their results fits in an increasing body of evidence, where pregabalin has shown to effectively prevent postoperative pain [ 2 ], potentially by reducing postoperative hyperalgesia and allodynia [ 3 , 4 ].…”
mentioning
confidence: 54%
“…It has been indicated that pregabalin reduce hyperalgesia and allodynia in human volunteers ( Chizh et al, 2007 ) and rat models ( Field et al, 1999 ). However, A J Lederer et al reviewed the effects of pregabalin on OIH and concluded that, despite strong support by theoretical considerations, the recommendation as a clinical use still lacks clinical evidence ( Lederer et al, 2011 ). Stoicia et al reached a similar conclusion, stating that applying gabapentin in mitigating OIH still requires support from large-scale standardized patient studies ( Stoicea et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%